Isolation of endophytic bacteria from cashew root and its ability as phosphate solubilizing and IAA-producing bacteria - Yulia Ningsih; Lalu Zulkifli; Mahrus Mahrus (Jurnal Biologi Tropis, 2022)
This study aimed to isolate endophytic bacteria from cashew plant roots, and to determine their ability to dissolve phosphate and produce IAA. This research was conducted at the Microbiology Laboratory of the Faculty of Medicine, University of Mataram. This research was conducted by isolating the endophytic bacteria of cashew nut root and then testing the phosphate solubilizing ablity and testing the potential for IAA-producing bacteria. Based on the results of the study, there were 7 isolates of endophytic bacteria, all of which were able to solubilize inorganc phosphate with a low phosphate solubility index, ranging from 1 to 1.7. Of the 7 isolates, there were 2 isolates that were able to produce IAA, namely AJM 7 and AJM8 isolates with IAA concentrations ranging from 16 to 18 ppm. Based on the results above, it can be concluded that the endophytic bacterial isolates from the roots of the cashew plant have the potential to be a candidates for biofertilizer formulation.